DOP66 The effect of exclusive enteral nutrition on circulating inflammatory protein levels in paediatric patients with Crohn's Disease. (27th May 2021) - Pidoux, M; Logan, M; Milling, S; Ijaz, U Z; Hansen, R; Russell, R K; Gerasimidis, K
Abstract: Background: Exclusive enteral nutrition (EEN) is the recommended first line treatment for active paediatric Crohn's disease (CD). The mechanism of action and immunological effects of EEN remain unclear. This study compared circulating inflammatory proteins of patients with CD and ulcerative colitis (UC) with non-inflammatory bowel disease (non-IBD) controls and explored the effect of EEN in children with active CD. Methods: Patients with CD were treated with EEN for 8 weeks, with plasma samples collected prior to EEN start and upon EEN completion. Levels of 92 inflammatory proteins were quantified using Olink Inflammation panel. Paired faecal samples were collected to measure faecal calprotectin (FC) levels by ELISA. Patients in which FC decreased >50% during EEN were classed as FC responders; whereas patients who had a <50% decrease in FC were classed as FC non-responders. Results: 84 patients were recruited (CD:54, UC:11, non-IBD:19). Paired plasma samples were collected from 18 patients with CD receiving EEN. Of these 18 patients, 72% achieved clinical remission by the end of EEN (wPCDAI <12.5 points). Prior to EEN start, 29 proteins were significantly different between patients with CD compared to non-IBD; and 25 proteins were significantly different between UC and non-IBD, Fig 1. EEN lead to the significant alteration of 23 proteins. This included 5 proteins, CCL23, CXCL10, IL6, IL24, and MMP-1 which were higher in patients with CD prior to EEN start compared to non-IBD, Fig 2. In patients who achieved clinical remission during EEN, 22 proteins significantly changed from their EEN start levels by the end of EEN, Fig 3. FC responders had a similar pattern of protein changes, in which 22 proteins changed significantly during EEN, Fig 4. 16/22 (72%) of the proteins that changed significantly in the FC responder group during EEN, also changed during EEN in patients who entered clinical remission including significant reductions in several innate immune proteins such as IL-6 and IL-18. Patients who did not achieve clinical remission did not have significant reductions in these proteins. Despite being higher in patients with CD prior to treatment compared to non-IBD, the level of 17 proteins, including IL17a and oncostatin M, did not change in FC responders during EEN. Conclusion: EEN leads to alteration of multiple inflammatory proteins, in keeping with a reduction in innate immune pro-inflammatory activity and improvement in clinical response, although some inflammatory proteins remain elevated. Figure 1: Venn diagram of proteins significantly different Figure 2: Effect of EEN on protein levels Figure 3: Effect of EEN on protein levels, stratified based on clinical response during EEN Figure 4: Effect of EEN on protein levels, stratified based on FC response